Effect of surface roughness on adhesion strength in ultrasonic soldering of glass - Mohd. Yusry, Mustafa; Irfan, Hilmy; Erry Yulian Triblas, Adesta (Asian Research Publishing Network (ARPN), 2015)
The research focused on improving the adhesion strength of low melting temperature lead free solder to soda lime glass through ultrasonic soldering. This was conducted by analyzing the effect of glass surface roughness on shear separation strength and shear separation energy between glass and solders. Analysis was conducted through tensile stress test. Other soldering parameters involving temperature, time, vibration amplitude, solder alloys and frequency were kept constant. (Sn40Bi)0.3Mg and (Sn40Bi)0.5Al solder alloys were selected due to their low melting temperatures and good adhesion to glass. Shear separation strength and extension before fracture data from the tensile stress test was used to derive shear separation energy values. Solder adhesion strength and solder adhesion energy between solder alloys and glass improved with increasing glass surface roughness. Study on bonding mechanism was conducted by using scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDX). Bond between ultrasonic soldering of glass and solder alloys consists of metal oxide adhesion and mechanical adhesion.